Performance of high-sensitivity cardiac troponin T versus I for the early diagnosis of myocardial infarction. (3rd October 2022) - Koechlin, L; Boeddinghaus, J; Lopez-Ayala, P; Nestelberger, T; Miro, O; Wussler, D; Zimmermann, T; Strebel, I; Christ, M; Wildi, K; Rubini Gimenez, M; Martin-Sanchez, J; et al.
Abstract: Background: Clinical practice guidelines assume that both cardiac troponin (cTn) T and cTnI concentrations reflect identical pathophysiological processes and are equally effective in the detection of myocardial injury. However, there are differences between cTnT and cTnI that have been reported. Purpose: The aim of this study was to directly compare the diagnostic performance of high-sensitivity cardiac troponin (hs-cTn) T versus hs-cTnI for the early diagnosis of acute myocardial infarction (MI). Methods: In a prospective multicentre study, diagnostic and prognostic accuracies of hs-cTnT and I were analyzed in consecutive patients presenting to the emergency department with acute chest pain. The final diagnosis was adjudicated by two independent cardiologists using all information pertaining to the individual patient according to the fourth universal definition of MI. Adjudication of the final diagnoses was performed twice: once using serial measurements of hs-cTnT and once using hs-cTnI. Furthermore, the clinical performance of hs-cTnT/I when embedded in the European Society of Cardiology (ESC) 0/1h-algorithm was assessed. Results: Among 5087 consecutive patients (median [Interquartile range, IQR] age 61 [49.0, 74.0] years, 33.2% female), 951 (18.7%) and 901 patients (17.7%) had an adjudicated final diagnosis of non-ST-segment elevation myocardial infarction (NSTEMI) when using serial measurements of hs-cTnT and hs-cTnI for adjudication, respectively. Diagnostic accuracy was very high for both hs-cTnT and hs-cTnI and comparable when using hs-cTnT for adjudication (hs-cTnT: area under the curve [AUC] 0.93 [95% CI 0.92–0.94] versus hs-cTnI AUC 0.93 [95% CI 0.92–0.94]; p=0.891). However, when using serial measurements of hs-cTnI for adjudication, diagnostic accuracy was significantly higher for hs-cTnI (AUC 0.93 [95% CI 0.92–0.94] versus AUC 0.94 [95% CI 0.94–0.95], p<0.001; Figure 1). This was confirmed in subgroup analyses including early presenter (≤3h), patients with renal failure, known coronary artery disease and elderly (≥70 years). However, both assays performed excellent with very high safety for rule-out and high accuracy for rule-in MI when embedded in the ESC 0/1h-algorithm. Prognostic accuracies for 730-day all-cause mortality and cardiovascular death were significantly higher for hs-cTnT compared to hs-cTnI (Figure 2). Conclusions: While there seem to be differences between hs-cTnT and hs-cTnI in their diagnostic and prognostic performance, clinical relevance needs to be further evaluated since both assays performed excellent when embedded in their respective early triage algorithms. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swiss National Foundation, Swiss Heart Foundation